The Influence of the Heating Rate on the Microstructure and Mechanical Properties of a Peak Annealed Quenched and Partitioned Steel - Castro-Cerda, F; Hernandez-Duran, E (Elsevier Ltd, 2020)
In this study an Fe-0.28C-1.91Mn-1.44Si cold-rolled steel was subjected to conventional (10 °C/s) and ultrafast (100 °C/s - 700 °C/s) heating peak annealing treatments, followed by quenching and partitioning (Q&P). The microstructural characterization results showed that grain refinement of the parent austenite and its transformation products occurred with the increment of the heating rate from 10 °C/s to 100 °C/s, without further refining at 700 °C/s. The formation of complex microstructures after the end of the thermal treatment, accompanied by the reduction in the retained austenite carbon content, suggested that local chemical heterogeneities in austenite appear upon ultrafast heating. Regardless of the prior heating rate, similar mechanical properties and strain hardening were measured, revealing that both, the microstructure development and the extent of austenite stabilization during quenching and partitioning stage play a fundamental role on the mechanical behavior of the peak annealed Q&P steels. © 2020 Elsevier B.V.